Pengaruh Penggunaan Buku Ajar Berbantu Kartu Kuartet Terhadap Kemampuan Literasi Sains Biologi dan Motivasi Belajar Siswa Kelas XI SMA - Adnan Adnan; Salmawati Salmawati; Usman Usman; Suhardi Aldi (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
This study utilized a quasi-experimental research design in the form of a pretest-posttest control group. It aimed to examine the impact of textbooks assisted by quartet cards on science literacy skills and student learning motivation. The research sampling was conducted through a simple random technique, selecting XI MIPA 5 class as the treatment group and XI MIPA 3 as the control group. Data was collected using multiple-choice tests to measure science literacy skills and questionnaires to assess student learning motivation. The descriptive and inferential analyses were conducted, employing non-parametric tests (Mann-Whitney) as the data analysis technique in this study. The results of the descriptive analysis illustrated that students taught with textbooks assisted by quartet cards exhibited science literacy skills in the medium category, while their learning motivation was rated as very high. Based on the results of the inferential analysis, a significant difference was observed in the science literacy skills and learning motivation between students using textbooks assisted by quartet cards in the treatment class and those in the control class. The mean rank number in the treatment class consistently exceeded that of the control class in Biology at SMA Negeri 1 Wonomulyo. One limitation of the research is the shortage of quartet cards available for the learning process, which resulted in students taking turns rather than playing simultaneously. To address this, the teacher should prepare additional sets of cards, each accommodating four students, and effectively allocate time during the process of playing cards and answering questions in the textbooks. This will ensure that the learning process runs efficiently and effectively.